Correlation Between Liver Stiffness and Diastolic Function, Left Ventricular Hypertrophy, and Right Cardiac Function in Patients With Ejection Fraction Preserved Heart Failure - Zhang, Junyi; Xu, Mingzhu; Chen, Tan; Zhou, Yafeng (Frontiers in Cardiovascular Medicine, 2021)
Objective The relationship between liver stiffness (LS) and ejection fraction preserved heart failure (HFpEF) remains unclear. The purpose of this study was to explore the correlation between LS and HFpEF. Method We performed a prospective observational study. After accepting liver transient elastography on admission, consecutive 150 hospitalized HFpEF patients were divided into three groups based on their liver elasticity value: first-third quartiles. Left ventricular diastolic function, left ventricular hypertrophy degree, right cardiac function and short-term prognosis (≤1 year) were compared among the three groups, and the correlation between liver elasticity and each indicator was analyzed. Results The elasticity of the liver was abnormally high in more than two-thirds of cases. In terms of diastolic function and left ventricular hypertrophy, the ventricular septal e’ (5.01±2.69vs.6.48±2.29, P=0.025), lateral wall e’ (6.63±3.50vs 8.62±2.73,P=0.013), mean E/e’ (20.06±7.53vs 13.20±6.05,P=0.001), left atrial volume index (43.53±10.94vs.35.78±13.86,P=0.008), tricuspid regurgitation (TR) peak flow rate (3.16±0.44vs.2.75±0.50,P<0.001), left ventricular mass index (LVMI) in male (163.2±47.6vs.131.3±38.0,P=0.015) and in female (147.4±48.6vs.110.6±24.3,P=0.036) was significantly different between the third quartile and the first quartile. In terms of right cardiac function, right ventricular fractional area change (RVFAC)(30.3±5.4vs.36.5±6.8, P<0.001), tricuspid annular plane systolic excursion (TAPSE)(7.7±5.2vs.14.8±5.9, P=0.010), pulmonary systolic pressure (38.0±10.5vs.32.4±10.3, P=0.005), TR peak flow rate (3.16±0.44vs.2.75±0.50,P<0.001), and inferior vena cava diameter (2.53±0.51vs.1.98±0.41,P<0.001) were significantly different between the third quartile and the first quartile. Compared to HFpEF without RVD, HFpEF with RVD had higher liver elasticity value (7.95±0.60vs.7.31±0.84,P=0.003).The incidence of adverse cardiovascular events was significantly higher in the third quartile than in the first quartile (P=0.003) and the second quartile (P=0.008). Multivariate Cox proportional hazard analysis showed that adverse cardiovascular events were independently associated with NYHA class, atrial fibrillation, lg NT-proBNP, and liver elasticity value (HR=1.208, 95%ci 1.115-1.352,P=0.002). Conclusion Increase of liver stiffness is common in HFpEF patients. Increased liver stiffness in HFpEF patients was significantly associated with worsen left diastolic function, left ventricular remodeling, and the right cardiac function. Increased elasticity value were significantly associated with HFpEF combined with RVD. Atrial fibrillation, poorer NYHA class, higher NT-proBNP, and increased liver elasticity value were independent predictors of poor short-term prognosis of HFpEF patients.